Tell me a story a phonostylistic analysis of Maria Elena Paterno's "Sampaguita" - Manuel, Emily L. (College of Arts and Letters, University of the Philippines Diliman, 1996)
This study is an attempt to investigate the distinct features of the language of children's stories, particularly that of maria Elena Paterno, entitled "Sampaguita". A phonostylistc analysis was made, using Elizabeth Traugott and Mary Louise Pratt's theory on phonological cohesion and Brent Vine's theory on phonetic repetition, in order to determine whether or not the writer's style reflected the notion that children's literature differs from adult literature in degree but not in kind. The basic question asked were: Supposing that children's literature differs from adult literature in terms of degree and not in kind, can we still analyze a children's story, in much the same way that we analyze adult literature? Can Traugott and Pratt's theory on phonological cohesion, and Vine's theory on phonetic repetition be applied? The conclusion which has been deduced from these findings is that up to a certain extent, the ideas and the language of "Sampaguita" did exhibit a certain degree of 'complexity', in that it used similar stylistic devices and ideas of profundity (such as ambivalent concepts) as it would in adult literature. However, it has also been deduced that this degree of profundity, as shown by the phonostylistic analyses, is made up of cohesive and repetitive phonological material, linguistically accounting for a certain degree of 'simplicity' in the text.